mRNA therapy restores euglycemia and prevents liver tumors in murine model of glycogen storage disease - Jingsong Cao (Nature Portfolio, 2021)
Glycogen Storage Disease 1a (Gsd1a) is an inherited disorder caused by glucose 6-phosphatase (G6Pase-α) deficiency and characterized by hypoglycaemia and high risk of liver cancer. Here the authors develop a mRNA-based G6Pase-α delivery therapy that is efficacious and safe in a mouse model of GSD1a.